Current concept of oral health and its potential implications for policy and practice of dental health coverage and insurance: post COVID-19 measurement - Che Musa, Muhd Firdaus; Ab. Halim, Noorhazayti; Sayed Kamar, Syarifah Haizan; Abllah, Zurainie; Supa'at, Salwana; Mohd Ibrahim, Mohamad Shafiq (IIUM Press, 2021)
This review paper aims to succinctly discuss the current concept and definition of general and oral-health and its potential implications on policy and practice in regards to the dental health coverage/insurance post COVID-19 pandemic. In general, dental policies and coverage are treatment-oriented, largely focus on curative procedures with some portion for preventive care despite most of dental diseases being largely preventable. There is however still no universal consensus definition of health, leading to mixed-feeling in setting-up priorities and direction for health policy. The FDI-World Dental Federation has then published a new definition of oral-health, highlighting the broader determinants of oral-health and envisioning a discussion on the implications of this definition and, in particular, how to transform the new oral health framework into a policy and practice agenda. In Malaysia, it is predicted there will be increasing demand for public dental coverage post COVID-19, however the government is yet to be ready in fulfilling those needs, leading to worsening oral-health inequalities. The lack of healthcare expenditure with no health social insurance model reduces the affordability and accessibility of patients to private services. Moreover, such narrow definition of oral-health, as influenced by the previous policies led to a limited coverage for common dental diseases, including oral health-related deformities linked to oral cancer and injuries. These are the major challenges for Malaysia. The government should therefore working in partnership, start subsidising dental fees of private health insurance, focus and integrate disease prevention and health promotion in order to achieve WHO-goal of universal health coverage.